1978
DOI: 10.23986/afsci.71979
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of plant nutrients from cultivated soils: I Leaching of cations

Abstract: Leaching of native and added basic cations was studied in a lysimeter experiment. The trial was carried out with three surface soil samples: sand, fine sand and sandy clay. The effect of the acidic precipitation on the leaching losses was studied by using 0.025 M sulfuric acid as irrigation solution. The cation concentration in the leachate seemed to be determined by the CEO of the soil sample. The relative and absolute leaching losses were lowest in the sandy clay and highest in the sand soil. Five percolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…According to Hartikainen (1978b), the tendency for cations to be leached from different soils seems to depend on the cation exchange capacity of the soil. In somewhat acid mineral soils of Finland, the effective T. Yliiranta et al cation exchange capacity (CEC) appears to be most closely correlated with the clay content (Kaila, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…According to Hartikainen (1978b), the tendency for cations to be leached from different soils seems to depend on the cation exchange capacity of the soil. In somewhat acid mineral soils of Finland, the effective T. Yliiranta et al cation exchange capacity (CEC) appears to be most closely correlated with the clay content (Kaila, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Cations and anions are likely to be washed out in equivalent amounts. Comparing the sums of leached anion equivalents to the respective sums of the basic cations calculated from the analytical data from the previous work (Hartikainen 1978) it was found that the amounts of anions were always considerably lower than those of the cations. The chloride content was less than 1 meq in all the lysimeters and can be neglected.…”
Section: Resultsmentioning
confidence: 81%
“…In different soils it seems to correspond to the behaviour of cations (cf. Hartikainen 1978): leaching losses were lowest in the clay soil and showed a tendency to increase when soil material became coarser. However, phosphate makes a striking exception; the amounts washed out from the columns of sand and fine sand soils were at most about one tenth of the losses from the clay soil sample.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The effects of fertilization on the nutrient content of the subsoil are difficult to study, because they require special arrangements. The results of leaching experiments carried out in fields and in laboratory indicate the movement of basic cations (Wiklander 1970, Hartikainen 1978 to be greater than that of phosphorus (Hartikainen 1978 b).…”
Section: Introductionmentioning
confidence: 99%